Plasticity of monocytes and macrophages in cirrhosis of the liver - Geng, Anne; Flint, Emilio; Bernsmeier, Christine (Frontiers in Network Physiology, 2022)
Cirrhosis of the liver is a systemic condition with raising prevalence worldwide. Patients with cirrhosis are highly susceptible to develop bacterial infections leading to acute decompensation and acute-on-chronic liver failure both associated with a high morbidity and mortality and sparse therapeutic options other than transplantation. Mononuclear phagocytes play a central role in innate immune responses and represent a first line of defence against pathogens. Their function includes phagocytosis, killing of bacteria, antigen presentation, cytokine production as well as recruitment and activation of immune effector cells. Liver injury and development of cirrhosis induces activation of liver resident Kupffer cells and recruitment of monocytes to the liver. Damage- and pathogen-associated molecular patterns promote systemic inflammation which involves multiple compartments besides the liver, such as the circulation, gut, peritoneal cavity and others. The function of circulating monocytes and tissue macrophages is severely impaired and worsens along with cirrhosis progression. The underlying mechanisms are complex and incompletely understood. Recent ‘omics’ technologies help to transform our understanding of cellular diversity and function in health and disease. In this review we point out the current state of knowledge on phenotypical and functional changes of monocytes and macrophages during cirrhosis evolution in different compartments and their role in disease progression. We also discuss the value of potential prognostic markers for cirrhosis-associated immuneparesis, and future immunotherapeutic strategies that may reduce the need for transplantation and death.